2018
DOI: 10.1016/j.nedt.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Improving evidence based practice in postgraduate nursing programs: A systematic review

Abstract: There is a paucity of empirical evidence supporting the best strategies to use in developing evidence based practice skills and/or research knowledge translation skills for Master's Nursing students. As a profession, nursing requires methodologically robust studies that are discipline specific to identify the best approaches for developing evidence-based practice skills and/or research knowledge translation skills within the university teaching environment. Provision of these strategies will enable the nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 35 publications
1
39
0
3
Order By: Relevance
“…Research studies have conclusively demonstrated positive relationships between this form of educator support (Prensky, ; Pape et al, ), and scholastic self‐determination (Abeysekera and Dawson, ; Barrett et al, ), and engagement (Hansen, ; Bradley et al, ; Brass et al, ). The practice of AST also contributes to the development of IM by providing a rationale for choices (Tai et al, ; Queen and Hess, ), empathizing with the perspectives of students (Ten Cate et al, ; Hickman et al, ), and minimizing the use of controlling language (Mohr et al, ; Lopes et al, ; Meza et al, ) in the teaching environment. These practices provide students with the opportunity to pursue unique individual goals (Woolley and Fishbach, ) and interests (Ezell et al, ; Agius et al, ), and satisfy their needs for autonomy (Woolley and Fishbach, ) and competence (Desy et al, ; Gauer and Jackson, ).…”
Section: Theoretical Basis Of Intrinsic Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Research studies have conclusively demonstrated positive relationships between this form of educator support (Prensky, ; Pape et al, ), and scholastic self‐determination (Abeysekera and Dawson, ; Barrett et al, ), and engagement (Hansen, ; Bradley et al, ; Brass et al, ). The practice of AST also contributes to the development of IM by providing a rationale for choices (Tai et al, ; Queen and Hess, ), empathizing with the perspectives of students (Ten Cate et al, ; Hickman et al, ), and minimizing the use of controlling language (Mohr et al, ; Lopes et al, ; Meza et al, ) in the teaching environment. These practices provide students with the opportunity to pursue unique individual goals (Woolley and Fishbach, ) and interests (Ezell et al, ; Agius et al, ), and satisfy their needs for autonomy (Woolley and Fishbach, ) and competence (Desy et al, ; Gauer and Jackson, ).…”
Section: Theoretical Basis Of Intrinsic Motivationmentioning
confidence: 99%
“…Most significantly, TBL offers students the opportunity to recognize gaps in their knowledge (Naumann et al, ; Kron et al, ; Hill et al, ), and identify their individual learning needs (Jordan and Foster, ; Kunda, ; Riley, ). While being somewhat similar to TBL, the PBL approach requires a higher level of student involvement (Kong et al, ; Bakon et al, ), since it aims is to make the task the focus of a whole term or academic year (Hickman et al, ). Therefore, both methods primarily focus on the achievement of realistic objectives (Walker et al, ; Chen et al, ) through relevant and goal‐oriented teaching (Jordan and Foster, ; Calvin and McDowell, ; Riley, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses who undertake postgraduate study feel more empowered to challenge poor clinical practice because of their enhanced leadership, critical thinking, and decision‐making skills (Casey et al, ; Clark et al, ). Nurses’ research and evidence‐based practice competencies too are attributed to postgraduate study (Grønvik, Ulvund, & Bjørkly, ; Hickman et al, ). Premised on a coherent body of such evidence over time, we developed a postgraduate course (master's degree) for qualified nurses in Mozambique to strengthen their clinical and research leadership capacity.…”
Section: Background and Contextmentioning
confidence: 99%